NEGOTIATING ISLAMIC INHERITANCE DISTRIBUTION WITHIN LOCAL CUSTOM AMONG THE SASAK MUSLIMS OF LOMBOK - Ani Wafiroh; Aisyah Wardatul Jannah; Arif Sugitanata (UIN Antasari Banjarmasin, 2025)
This study aims to identify the stages of transformation in inheritance distribution practices among the Sasak Muslim community in Rensing Bat Village, East Lombok, and to explain the process of change through William Fielding Ogburn’s theory of social change. Drawing on field research with a qualitative approach supported by in depth interviews, the findings indicate a gradual shift from a patriarchal customary system towards a distribution pattern that aligns more closely with the principles of afraid. This transformation unfolds in four stages, beginning with the dominance of men as the primary heirs, the emergence of a justice based awareness that opens space for women, a transition towards a bilateral system, and the use of hibachi as a culturally accepted mechanism of value adjustment that simultaneously preserves family harmony. Osborn’s analysis shows that this change follows the stages of invention, accumulation, diffusion and adjustment, reflecting a bottom up process of social transformation arising from collective moral consciousness rather than from external structural pressure. The findings affirm that legal reform does not always need to be institutional or imposed from above, but may develop through the gradual internalization of Islamic values within local culture. This study offers a novel contribution by providing an empirical account of how such internalization occurs organically within the customary system, demonstrating that changes in inheritance practices may evolve through value negotiation at the community level.